Analisis Kurs Valas Dengan Pendekatan Box-Jenkins: Studi Empiris Rp/Us$ Dan Rp/Yen, 1983.2 – 2000.3 - Hadi Kardoyo; Mudrajat Kuncoro (Economic Journal of Emerging Markets, 2002)
This paper attempts to analyse Rp/US$ and Rp/Yen exchange rates over the period 1983.2-2000.3. Using the Box-Jenkins approach, we tested various models to explain the behavior of Rp/US$ and Rp/Yen. The results supported both interest rate parity and purchasing power parity hypotheses for Rp/US$ exchange rates. In the case of Rp/Yen, however, the results supported purchasing-power parity hypothesis rather than that of interest rate parity. Moreover, Frenkel-Bilson, Dornbusch-Frankel, Hooper-Morton model cannot be applied to analyse Rp/Yen fluctuation. This study, accordingly, calls an urgency to stop a Bank Indonesia’s policy to restrict foreign exchange transactions to reduce the fluctuation of rupiah, as stated in Peraturan Bank Indonesia (PBI) No. 3/3/PBI/2001, since 12 Januari 2001.  Key words: valas (exchange rates), Box-Jenkins, purchasing power parity, interest rate parity.